STUDI PROFIT GROWTH: PENGARUH PROFITABILITAS DIMODERASI ANALISA PASAR PERUSAHAAN KOMPAS 100 - Ade Nahdiatul Hasanah; Tri Wahyuni Sukiyaningsih (Jurnal Manajemen, 2023)
The research focuses on the study of profit Growth (Profit Growth) which is influenced by profitability consisting of Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on assets (ROA), Return on Equity (ROE), Return on Investment (ROI), Return on Sales (ROS), Return on Capital Employed (ROCE) and moderated by market analysis represented by the Profit Earning Ratio (PER) ratio that occurs in Kompas 100 index companies for the period 2020-2022. The purpose of the study was to partially explain the influence of the ratios on profitability and profit growth, as well as the moderation model through market analysis. The research population is a company indexed by Kompas 100 during 2020-2022 with purposive sampling as a sampling technique, 41 samples of companies were obtained that were analyzed statistically. Analysis in the study consists of descriptive statistics and assumption testing and hypothesis testing. Through the statistical results of this study, NPM has an effect on profit growth, ROA has an effect on profit growth, ROE has an effect on profit growth, GPM, ROI, ROS and ROCE have no effect on profit growth. While PER does not moderate all profitability to profit growth.